2011
DOI: 10.4137/cmo.s7263
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors in the Treatment of Advanced Renal Cell Carcinoma: Focus on Pazopanib

Abstract: Advances in our understanding of renal cancer biology have led to a new treatment paradigm in renal cancer. Tyrosine kinase inhibitors (TKI), that target the intracellular kinase domain of the VEGF receptor, have become established as the most successful class of agent in this disease. Three TKIs are currently approved for use in patients with advanced disease. Newer, more potent inhibitors have reached phase III clinical testing, meaning others are likely to follow. In 2009, pazopanib became the most recent T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Hereby, the overexpression of proangiogenic factors and intense angiogenesis are a hallmark of many RCCs [8,9,10]. Recently, antiangiogenic drugs, such as tyrosine kinase inhibitors, have been approved for first-line therapy of RCC [11,12]. Because of these reasons, US assessment of blood flow may hold a significant potential not only for diagnostic purposes but also for monitoring therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Hereby, the overexpression of proangiogenic factors and intense angiogenesis are a hallmark of many RCCs [8,9,10]. Recently, antiangiogenic drugs, such as tyrosine kinase inhibitors, have been approved for first-line therapy of RCC [11,12]. Because of these reasons, US assessment of blood flow may hold a significant potential not only for diagnostic purposes but also for monitoring therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Vasudev and Larkin reported a phase III trial in which the most frequently reported AEs were diarrhea, hypertension, nausea, anorexia, and vomiting (5) [13]. The most common higher-grade toxicities (3/4) were hypertension (4%) and diarrhea (3%) (5) [13].…”
Section: Discussionmentioning
confidence: 99%
“…The most common higher-grade toxicities (3/4) were hypertension (4%) and diarrhea (3%) (5) [13]. Recent studies may indicate that the frequency of certain toxicities increase as the plasma concentration of pazopanib goes up (5) [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations